2009
DOI: 10.1111/j.1752-1688.2008.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Using SWAT to Model Streamflow in Two River Basins With Ground and Satellite Precipitation Data1

Abstract: Both ground rain gauge and remotely sensed precipitation (Next Generation Weather Radar -NEXRAD Stage III) data have been used to support spatially distributed hydrological modeling. This study is unique in that it utilizes and compares the performance of National Weather Service (NWS) rain gauge, NEX-RAD Stage III, and Tropical Rainfall Measurement Mission (TRMM) 3B42 (Version 6) data for the hydrological modeling of the Middle Nueces River Watershed in South Texas and Middle Rio Grande Watershed in South Tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 53 publications
3
51
0
Order By: Relevance
“…The NEXRAD data set led to an overestimated BFI by up to 23%, which was surprising considering that the level III NEXRAD data have been shown to produce more accurate hydrologic model performance compared to satellite-derived precipitation products, and a better choice for MAP inputs for hydrologic model performance than point gauges [56][57][58]. For example, Tobin and Bennett (2009) [58] used level III NEXRAD data for input into the SWAT model and the results showed that the three day average stream flow was associated with NSE values ranging from 0.60 to 0.88, while the TRMM 3B42 data set yielded more variable results with NSE values ranging from 0.38 to 0.94. However, in the current work, the NEXRAD precipitation data set was associated with the greatest overestimation in annual total precipitation (MAE = 152 mm) which indicated potential radar accuracy issues.…”
Section: Calibrated Model Performancementioning
confidence: 99%
“…The NEXRAD data set led to an overestimated BFI by up to 23%, which was surprising considering that the level III NEXRAD data have been shown to produce more accurate hydrologic model performance compared to satellite-derived precipitation products, and a better choice for MAP inputs for hydrologic model performance than point gauges [56][57][58]. For example, Tobin and Bennett (2009) [58] used level III NEXRAD data for input into the SWAT model and the results showed that the three day average stream flow was associated with NSE values ranging from 0.60 to 0.88, while the TRMM 3B42 data set yielded more variable results with NSE values ranging from 0.38 to 0.94. However, in the current work, the NEXRAD precipitation data set was associated with the greatest overestimation in annual total precipitation (MAE = 152 mm) which indicated potential radar accuracy issues.…”
Section: Calibrated Model Performancementioning
confidence: 99%
“…Soil and water assessment tool (SWAT) is a physical, semi-distributed hydrological model that has a few advantages in predicting climate change effects on water-related and hydrological processes over a continuous time [17]. The performance of this model relies on precipitation input parameters, namely accuracy and spatial distribution [18]. So, many researchers have selected grid precipitation to drive hydrological models.…”
Section: Introductionmentioning
confidence: 99%
“…Simulated bacterial concentrations were determined using the SWAT model. Tobin and Bennett [1] previously modeled the middle Rio Grande Basin, which overlaps with the study area, and this work provided information that facilitated model calibration. The precipitation dataset input into the model was the National Weather Service Multisensor Estimator product (MPE).…”
Section: Methodsmentioning
confidence: 99%